DOI: 10.18297/etd/2429
|View full text |Cite
|
Sign up to set email alerts
|

Exploring differences between the health and wellness of state police officers and community corrections professionals.

Abstract: DEDICATIONThis dissertation is dedicated to Brees and Ezra Copenhaver. Brees, you never cease to amaze me with the things you are able to do and the new skills you learn each day. Ezra, you are my little guy with those big baby blue eyes and his mommy's personality. I love you both so very much and I hope the completion of this dissertation is the beginning of a better life for both of you.iv ACKNOWLEDGMENTS I would like to thank my mentoring professor, Dr. Richard Tewksbury for his oversight on this project a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 142 publications
0
3
0
Order By: Relevance
“…Correlations between sleep and mood patterns are difficult to interpret, although they are frequently observed in research, because mood can cause a lack of sleep, or inversely, a lack of sleep can affect one’s mood (National Sleep Foundation, 2019). The relationship between officer depression and officers feeling in control of their jobs is not surprising given previous research has demonstrated an association between officers feeling in control of their jobs and significantly lower chances of experiencing depression (see Copenhaver, 2016). At the same time, research generally shows that depression correlates significantly with occupational stressors of law enforcement (Bhui, Dinos, Stansfeld, & White, 2012).…”
Section: Discussionmentioning
confidence: 88%
“…Correlations between sleep and mood patterns are difficult to interpret, although they are frequently observed in research, because mood can cause a lack of sleep, or inversely, a lack of sleep can affect one’s mood (National Sleep Foundation, 2019). The relationship between officer depression and officers feeling in control of their jobs is not surprising given previous research has demonstrated an association between officers feeling in control of their jobs and significantly lower chances of experiencing depression (see Copenhaver, 2016). At the same time, research generally shows that depression correlates significantly with occupational stressors of law enforcement (Bhui, Dinos, Stansfeld, & White, 2012).…”
Section: Discussionmentioning
confidence: 88%
“…Based on these results, it was concluded that the consumption of energy shots could compromise aiming accuracy and shot placement, thereby jeopardizing the health and welfare of law enforcement personnel (Monaghan et al, 2017;Monaghan et al, 2014). On the other hand, according to Copenhaver (2016), as officers consume more stimulant drinks per shift they also drink alcohol for a greater number of days per week, normally consume an alcoholic drink after work, sleep less, and consume more fast food. Based on previous studies, it was also assumed that CUD is more prevalent among females than males (H.2).…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of research on law enforcement officer health and wellness demonstrates that when officers experience mental health issues they have a difficult time completing the real-world requirements of their occupation. This means that if officers are struggling with mental health issues, or a lack of confidence, they may not be able to adequately to pursue suspects, detain suspects, or perform other tasks such as operating their patrol cars (Copenhaver, 2016). The literature in the area of officer confidence is most easily understood in terms of officer positive self-regard and physical confidence.…”
Section: Introductionmentioning
confidence: 99%